DAMPAK KEBIJAKAN PENGEMBANGAN PARIWISATA DENGAN PENDEKATAN EKOWISATA DI PULAU KARIMUNJAWA JEPARA - Hehalatu, Ansye (JI@P, 2015)
Tourism is one of the largest foreign exchange earner sectors in Indonesia. This is shown with more development strategy of tourism promotion and development policy with the ecotourism approach that are friendly to environment. Government and community are the two main elements of tourism development policy. Development of mass tourism in Karimunjawa become a major prop for the government. In terms of increasing local revenues for society, in the economic, social, cultural and educational. As for the environment, the development of mass tourism has tended to impact negatively. Environment should get special attention, so that the level of environmental damage to the ecosystem as a tourist attraction should be lower. The high possibility of damage to the ecosystem then force the goverment to take a new policy for Karimunjawa, such as, the development of mass tourism to ecotourism approach. Tourism is expected to bring the change for the benefit of the community, to give a good effect, in accordance with the existing policies and objectives. This study is aimed to examine the effects that arise in the process of implementation of the tourism development policy in Karimunjawa, along with the monitoring, handling and the responsibility of the government if what is happening have a negative impact. This research uses a qualitative approach, the method of taking data using in-depth interviews, the raw data from the various government agencies involved in the development of tourism in Karimunjawa, as well as the observation that done by researchers in Karimunjawa. In order to have data that more reliable and trustworthy. Results of the analysis showed: 1) there is an increase in local revenues in line with the increasing number of tourists who visit the Karimunjawa. 2) Changes that have occurred such as people’s income and enforced many new jobs. 3) A change in people’s behavior ranging from children up to adolescence. The low level of education or unstable personality, causing a person can easily influence by foreign cultures without having to be taught. 4) The principle of the development of mass tourism causing undeniable concern for communities to sustain tourism’s assets. It’s easy of making money instantly causing people of reluctanting to try to develop economy creative and small business. Keywords: Impact, Tourism, Ecotourism